Strength training and detraining in different populations: - Marques, M. C.; Zajac, A.; Pereira, A.; Costa, A. M. (Journal of Human Kinetics, 2011)
Many researchers have demonstrated that a specific strength training program can improve maximal strength and, the rate of force production, reduce the incidence of muscle-skeletal injury, and contribute to faster injury recovery times, thereby minimizing the number of missed practice sessions or competitions. Yet, to our best knowledge, there is no apparent consensus on the appropriate method of muscle strength and power training to enhance performance in distinct populations groups. Interruptions in training process because of illness, injury, holidays, post-season break or other factors are normal situations in any kind of sport. However, the detraining period and its consequences are not well reported in sports literature, and namely during puberty. Therefore, the aim of this paper was to discuss several case studies concerning different populations such us physical students, age-swimming competitors and elite power athletes.